The way of the shepherd ebook 7 ancient secrets to managing productive people. - Leman, Kevin (2009)
Discover a fresh perspective on the art of leading in Dr. Kevin Leman's story about a young reporter who lands the meeting of a lifetime and walks away with the keys to exceptional leadership. The Way of the Shepherd points you beyond dated trends and out-of-touch management techniques to the strategies that will make you a truly outstanding leader. When William Pentak had the once-in-a-lifetime opportunity to interview Ted McBride, one of the most respected CEOs in America, he was shocked by what McBride was willing to share. McBride taught him the seven secrets he inherited long ago from his mentor—an eccentric but brilliant professor who passed on these time-tested management principles that, while ancient in their origin, are still applicable in today's fast-paced, high-tech world. Throughout The Way of the Shepherd, you'll learn how to infuse your work with meaning, no matter your role, title, industry, or the size of your team. Uncover the tried-and-true best practices for how to engage, energize, and ignite your workforce by: Getting to know your team, one person at a time Relentlessly communicating your values and your mission Defining the cause for your people and showing them where they fit in Having a heart for the people that you're leading Understanding that great leadership isn't just professional, it's personal If you're ready to transform your team, create a culture of belonging, and truly learn to lead by example, it's time to discover The Way of the Shepherd.